Recent advances in physical delivery enhancement of topical drugs - Raphael, A.; Wright, O.; Benson, Heather; Prow, T. (2015)
© 2015 Bentham Science Publishers. The skin has evolved to resist the penetration of foreign substances and particles. Effective topical drug delivery into and/or through the skin is hindered by these epidermal barriers. A range of physical enhancement methods has been developed to selectively overcome this barrier. This review discusses recent advances in physical drug delivery by broadly separating the techniques into two main areas; indirect and direct approaches. Indirect approaches consist of electrical, vibrational or laser instrumentation that creates pores in the skin followed by application of the drug. Direct approaches consist of mechanical disruption of the epidermis using techniques such as microdermabrasion, biolistic injectors and microneedles. Although, in general, physical techniques are yet to be established in a clinical setting, the potential gains of enhancing delivery of compounds through the skin is of great significance and will no doubt continue to receive much attention.